Short-term experimental flooding impacts soil biogeochemistry but not aboveground vegetation in a coastal forest - Peter Regier; Ben Bond-Lamberty; Nicholas Ward; Vanessa Bailey; Roberta Bittencourt Peixoto; Fausto Machado-Silva; Nate McDowell; Kendalynn A. Morris; Allison Myers-Pigg; Stephanie C. Pennington; Mizanur Rahman; Roy Rich; et al. (Proceedings of the National Academy of Sciences, 2025)
Rising sea levels and intensifying storms increase flooding pressure on coastal forests, triggering tree mortality, ecosystem transitions, and changes to the coastal carbon cycle. However, the mechanisms that drive coastal forest mortality remain elusive due to the complex interplay between belowground and aboveground processes during flooding disturbances and limitations of observations typically reported in coastal forest mortality studies. We used an ecosystem-scale manipulation to simulate hurricane-level flooding of a coastal forest and explore the individual and interactive impacts of inundation and salinity. Monitoring real-time soil conditions and tree physiological responses, we observed consistent impacts on soil biogeochemistry aligned with belowground drivers of tree mortality, but no consistent responses in aboveground vegetation immediately following flooding. Our findings provide empirically based insight into the earliest stages of a hypothesized forest mortality spiral and offer critical benchmarks for predicting coastal forest resilience in the face of accelerating climate change.